Salt-affected Soils and their Managements - Rakshit, Amitava; Maiti, Ratikanta; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2010)
Accumulation of excessive salt in irrigated soils can reduce crop yields, reduce the effectiveness of irrigation, ruin soil structure, and affect other soil properties. This publication is designed to evaluate the kind and amount of salts resent in soils and to select management alternatives.